Otitis Externa - Atalay, Fatma (Nobel Tip Kitabevleri, 2024)
Otitis externa is a frequently painful inflammation widely seen in the external auditory canal, and that may be infectious or non-infectious. It can be classified according to the etiology, duration of disease, and localization. It is described as acute if it persists for less than six weeks, and as chronic if the duration exceeds three months. Otitis externa can be subclassified as acute otitis externa, chronic otitis externa, necrotizing otitis externa (malignant otitis externa), fungal otitis externa (otomycosis), herpes zoster oticus, bullous myringitis (hemorrhagic otitis externa), granular myringitis and furunculitis. The treatment of otitis externa is directed toward analgesia, treatment of underlying bacterial or fungal infection, and prevention of recurrence. Early diagnosis and treatment is important to prevent complications.